2001
DOI: 10.1175/1520-0477(2001)082<0889:taraan>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Aerosonde Robotic Aircraft: A New Paradigm for Environmental Observations

Abstract: The Aerosonde is a small robotic aircraft designed for highly flexible and inexpensive operations. Missions are conducted in a completely robotic mode, with the aircraft under the command of a ground controller who monitors the mission. Here we provide an update on the Aerosonde development and operations and expand on the vision for the future, including instrument pay loads, observational strategies, and platform capabilities. The aircraft was conceived in 1992 and developed to operational status in 1995-98,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(79 citation statements)
references
References 1 publication
0
78
0
Order By: Relevance
“…The new setup of ALADINA (Application of Light-weight Aircraft for Detecting in situ Aerosols) in the context of the ongoing development is provided as an introduction to the current modifications. The first applications date back to several decades ago [1]; later, some UAS applications of atmospheric research groups were reported in the 1990s [2]. Compared to these first meteorological applications, there has been a revolution concerning the functionality, size and complexity of even commercially available airborne systems, autopilots and the corresponding hardware and software.…”
Section: Introductionmentioning
confidence: 99%
“…The new setup of ALADINA (Application of Light-weight Aircraft for Detecting in situ Aerosols) in the context of the ongoing development is provided as an introduction to the current modifications. The first applications date back to several decades ago [1]; later, some UAS applications of atmospheric research groups were reported in the 1990s [2]. Compared to these first meteorological applications, there has been a revolution concerning the functionality, size and complexity of even commercially available airborne systems, autopilots and the corresponding hardware and software.…”
Section: Introductionmentioning
confidence: 99%
“…The Aerosonde ® UAS is a small (3.6 m wingspan, 19-21 kg takeoff weight), robotic, pusher-prop aircraft designed to undertake a wide range of operations in a highly flexible and inexpensive mode (see Table 1 for the specifications of the Aerosonde ® UAS). The Aerosonde ® UAS has proven to be capable of carrying a variety of instrument packages (Holland et al, 2001) and to perform well under polar winter conditions in the Arctic (Inoue and Curry, 2004;Inoue et al, 2008) and the Antarctic (Cassano et al, 2010;Knuth et al, 2013). The relatively fast flight speed for a small UAS allows the Aerosonde ® UAS to operate in strong winds, which are a frequent feature of the Terra Nova Bay region.…”
Section: Aerosonde Uasmentioning
confidence: 99%
“…There have, however, been a couple of meteorological experiments involving unmanned aerial vehicles (UAVs) [7,8,9]. The advantage of these UAVs is that it is possible to perform the measurements along previously defined spatial coordinates.…”
Section: Advantages Over Other Similar Devicesmentioning
confidence: 99%